Occupational Therapy at home: Palliative Care Approach - Pedrosa, Vanda Varela (2020)
The workshop The Occupational Therapy (OT) in the Palliative Care (PC). We hope it can contribute, in a valuable way to preserve independence, comfort and quality of life, effectively during illness and even death. Home, is the holistic and multiprofessional intersection of doing with the person, the caregivers, in their environment, the place where the OT can play a very relevant role in the place, facilitating the improvement of the quality of life especially when we speak of intervention in PC As been presented in 24th Annual Meeting 2018.